ANALISIS RISIKO PROYEK PEMBANGUNAN SITUS MUARO JAMBI RISK ANALYSIS OF THE MUARO JAMBI HISTORICAL SITE DEVELOPMENT PROJECT - Dwiyanto, Muhaswad; Supriadi, Yudi Nur (Gapenas Publisher, 2025)
The Muaro Jambi site, which is recognized as a Cultural Heritage through the Decree of the Minister of Education and Culture of the Republic of Indonesia Number 259/M/2013, has an important value as the nation's cultural heritage. As part of preservation efforts, the site has a vital role in understanding and developing history, science, and culture. Therefore, its management needs to be carried out appropriately through protection, development, and utilization that can support the progress of national culture for the welfare of the community. As part of this utilization step, the Muaro Jambi Site development project will begin in 2024. To ensure that this project is carried out efficiently, effectively, and accountably, a risk analysis of various activities related to this project is carried out. The results of risk identification in the early stages of the project revealed that there were 62 risks related to museum construction, 52 risks to environmental arrangement, 63 risks to restoration, and 53 risks related to interior activities and Information Communication and Technology (ICT). These risks include operational, financial, legal, fraud, as well as strategic and policy risks. From the results of the analysis, it can be concluded that the identification of risks in all project activities shows significant similarities, although there are slight differences due to the specific nature of each activity. In addition, there are several key risks that need to be seriously considered to ensure the achievement of project objectives, namely budget blocks, cultural heritage findings during excavation, and lack of involvement of the surrounding community in the sustainability of the project. Therefore, high and very high levels of risks must be addressed immediately with appropriate mitigation, while medium-level risks can be monitored on an ongoing basis. Risks with low levels still need to be monitored to prevent greater negative impacts